1980
DOI: 10.1002/jmor.1051630109
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure and functions of haemerythrocytes and leucocytes of Sipunculus nudus

Abstract: The marine sipunculan worm, Sipunculus nudus Linné, possesses a voluminous coelomic cavity filled with a fluid containing different types of free cells. Most of them (more than 90%) are nucleated haemerythrocytes. They arise from free, small haemerythroblastic cells which are described in this report. Different kinds of leucocytes are also found in the coelomic fluid, particularly granulocytes which are phagocytic cells showing some similarities with vertebrate macrophages. These cells seem to arise from small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…They do not form the thick sheath around the nerve that Baskin (1971) described but neither are they exposed to as much stress as the polychaete ventral nerve. (Valembois and Boiledieu 1980) in most respects except that mitochondria were not seen in Themiste. Phagocytosis has been observed in sipunculan blood cells (Cuenot 1913;Chapheau 1928) and probably accounts for the vacuoles of electron dense particles in Themiste hemocytes.…”
Section: Discussionmentioning
confidence: 94%
“…They do not form the thick sheath around the nerve that Baskin (1971) described but neither are they exposed to as much stress as the polychaete ventral nerve. (Valembois and Boiledieu 1980) in most respects except that mitochondria were not seen in Themiste. Phagocytosis has been observed in sipunculan blood cells (Cuenot 1913;Chapheau 1928) and probably accounts for the vacuoles of electron dense particles in Themiste hemocytes.…”
Section: Discussionmentioning
confidence: 94%
“…The ubiquity of cell killing is evident in other reports which describe cytotoxic reactions in five different invertebrate phyla: Sipunculoidea (38,39]. Annelida [25,37], Mollusca [40].…”
Section: Cytotoxicitymentioning
confidence: 92%
“…in turn, induces a second leucocyte to kill target cells in a non-specific manner. Only the killer eells have been observed by microscopy [38]; they are small hyalocytes or granulocytes with few granules and numerous ribosomes. As seen by both electron microscopy and time-lapse microcinematography.…”
Section: Cytotoxicitymentioning
confidence: 99%
“…Therefore, they have been used as experimental animals to investigate cellular and humoral immune reactions. In in vivo and in vitro studies, the granulocytes have been observed to be the main phagocytic cells in Sipunculus nudus (Cuenot, 1900;Cantacuzene, 1922;Volkonsky, 1933;Valembois and Boiledieu, 1980), Phascolosoma vulgare (Volkonsky, 1933), and Phascolosoma agassizii (Towle, 1962;Blitz, 1965). However, Brown and Winterbottom (1969) injected thorium dioxide into the coelomic cavity of Golfingia capensis, a species without ciliated urns, and observed that all coelomic cells ingested the thorium particles.…”
Section: Introductionmentioning
confidence: 99%